Partai Golkar Pada Masa Orde Baru Di Gorontalo Tahun 1977-1998 - Saleh, Owen; Djako, Yulinda; Karim, Sukarni A (Jambura History and Culture Journal, 2022)
This article aims to find out about the New Order Golkar Party in Gorontalo. The Golkar Party was the strongest party during the Soeharto era, the Golkar party was born from an organization called the Golkar Secretariat or the Joint Secretariat of Golkar. During the Soeharto era, this political party became the government party, which every time a general election was held, it always won. In the period 1977 to 1998 elections were held in the province of Gorontalo. Likewise, Gorontalo feels the same way with other regions. The Golkar Party which at that time became the dominant party of the other two parties, namely PDI and PPP. The three parties during the New Order era that were more powerful and still stronger than the government were the Golkar party.